Downregulation of Fat Mass and Obesity Associated (FTO) Promotes the Progression of Intrahepatic Cholangiocarcinoma - Rong, Zhuo-Xian; Li, Zhi; He, Jun-Ju; Liu, Li-Yu; Ren, Xin-Xin; Gao, Jie; Mu, Yun; Guan, Yi-Di; Duan, Yu-Mei; Zhang, Xiu-Ping; Zhang, De-Xiang; Li, Nan; et al. (Frontiers in Oncology, 2019)
Intrahepatic cholangiocarcinoma (ICC) ranks as the second most malignant type of primary liver cancer with a high degree of incidence and a very poor prognosis. Fat mass and obesity-associated protein (FTO) functions as an eraser of the RNA m6A modification, but its roles in ICC tumorigenesis and development remain unknown. We showed here that the protein level of FTO was downregulated in clinical ICC samples and cell lines and that FTO expression was inversely correlated with the expression of CA19-9 and micro-vessel density (MVD). A Kaplan-Meier survival analysis showed that a low expression of FTO predicted poor prognosis in ICC. In vitro, decreased endogenous expression of FTO obviously reduced apoptosis of ICC cells. Moreover, FTO suppressed the anchorage-independent growth and mobility of ICC cells. Through mining the database, FTO was found to regulate the integrin signaling pathway, inflammation signaling pathway, EGFR signaling pathway, angiogenesis and the pyrimidine metabolism pathway. RNA decay assay showed that oncogene TEAD2 mRNA stability were impaired by FTO. In addition, the overexpression of FTO suppressed tumor growth in vivo. In conclusion, our study demonstrated the critical roles of FTO in ICC.